Discrimination against water containing unrelated conspecifics and a marginal effect of relatedness on spacing behaviour and growth in juvenile brown trout, Salmo trutta L. - Ojanguren, A F; Brana, F (1999)
In this study, we assessed whether juvenile brown trout are able to discriminate between, and swim towards, water containing unrelated conspecifics and blank stream water. In a second stage we investigated the behavioural response to sibling-scented vs. nonsibling conspecific-scented water, and how the social environment could affect growth. All the six families (full sibs) tested showed an overall preference to blank water instead of water scented by unfamiliar fish of similar age and size. This result reveals that juvenile brown trout are able to detect chemical water components released by conspecifics, and show a biased behaviour based on this ability. When trout were given the choice between water scented by sibs and unfamiliar nonsibs, results were variable, some families spent more time in the sibling-scented water channel (only significant for one of six families) while others showed the opposite trend. Large within-family variation was also observed in the responses of individual fish towards water scented by siblings and nonsiblings. When fish from three of the families were reared with either siblings or nonsiblings, we obtained results that were only partially consistent with the hypothesis that fish growth could be enhanced in the preferred social environment (which had been predicted from the results of the choice tests).